2019
DOI: 10.1080/22221751.2019.1688097
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Aedes albopictus and Aedes aegypti (Diptera: Culicidae) to transmit yellow fever virus in urban areas in Central Africa

Abstract: Yellow Fever (YF) remains a major public health issue in Sub-Saharan Africa and South America, despite the availability of an effective vaccine. In Africa, most YF outbreaks are reported in West Africa. However, urban outbreaks occurred in 2016 in both Angola and the Democratic Republic of Congo (DRC), and imported cases were reported in Chinese workers coming back from Africa. In Central Africa, Cameroon and the Republic of Congo host a high proportion of non-vaccinated populations increasing the risk of urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…aegypti and Ae. albopictus from Brazzaville, are able to ensure yellow fever virus [35], dengue virus [37], Zika virus [36] transmission. To clearly establish the epidemiological importance of each Aedes species in the Republic of the Congo, additional experiments including feeding behaviour patterns, covering additional locations, and spanning several seasons are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti and Ae. albopictus from Brazzaville, are able to ensure yellow fever virus [35], dengue virus [37], Zika virus [36] transmission. To clearly establish the epidemiological importance of each Aedes species in the Republic of the Congo, additional experiments including feeding behaviour patterns, covering additional locations, and spanning several seasons are needed.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti and Ae. albopictus collected in Brazzaville are able to transmit yellow fever virus [35], Zika virus [36], and dengue virus [37]. As there is no efficient vaccine (apart from yellow fever) and specific treatment against these diseases, vector control remains the cornerstone to prevent outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…It was also demonstrated that local Ae. aegypti populations are able to transmit dengue [ 11 ], Zika [ 12 ] and yellow fever [ 13 ] viruses in different urban settings in Cameroon. Prevention of large outbreaks caused by these virus relies on control of Aedes vectors based on destruction of breeding sites and insecticide-based interventions such as treatment of breeding sites with larvicides, insecticide-treated nets [ 14 ] and space spraying of adulticides in emergency situations [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…After egg hatching, around 200 larvae were distributed per pan containing one liter of dechlorinated water and yeast tablets as food. Larvae were reared until the adult stage in controlled conditions 54 . OF1 mice for feeding mosquitoes were between 6-week and 2-month-old, maintained in an animal facility under standard conditions (23 °C and 14:10 light/dark cycle) at Institut Pasteur.…”
Section: Methodsmentioning
confidence: 99%
“…aegypti populations from the Asia-Pacific region compared to mosquitoes from YFV-endemic regions in Africa, we included mosquito populations from Cameroon (Benoué, Douala, and Yaoundé) and Congo (Brazzaville) to our dataset; African Ae. aegypti analyzed were partly processed in the previous publication of Kamgang et al 54 .…”
mentioning
confidence: 99%